Pathological and Genomic Findings of Erysipelothrix rhusiopathiae Isolated From a Free-Ranging Rough-Toothed Dolphin Steno bredanensis (Cetacea: Delphinidae) Stranded in Korea - Lee, Kyunglee; Park, Seon Young; Seo, Hwi Won; Cho, Yuna; Choi, Seok-Gwan; Seo, Seunghyun; Han, Wonmin; Lee, Nam-Kyung; Kwon, Hyemin; Han, Jee Eun; Kim, Ji Hyung (Frontiers in Veterinary Science, 2022)
Erysipelas, caused by Erysipelothrix rhusiopathiae, is considered one of the most serious infectious diseases of captive and free-ranging cetaceans worldwide, as these animals are known to be highly susceptible to the bacterial infections. The potential diversity between E. rhusiopathiae isolates from captive cetaceans has been previously described; however, the microbiological features of the free-ranging cetacean isolates remain unclear. Here, we describe a case of bacteremia in a rough-toothed dolphin (Steno bredanensis) caused by E. rhusiopathiae. Additionally, we present the first genomic features of the bacteria from free-ranging cetacean individuals. Histopathological and microbial examinations revealed that E. rhusiopathiae caused bacteremia and systemic infection in the dolphin. The genome of the isolated E. rhusiopathiae strain KC-Sb-R1, which was classified as Clade 1 possessing SpaB gene, was clearly differentiated from the other swine-isolated E. rhusiopathiae, and the comparison of its serovar-defining chromosomal region revealed that our isolate was greatly similar to those of other previously reported serovar 2/15 isolates, including the captive-dolphin isolate. Moreover, most of the potential virulence factors in the strain KC-Sb-R1 were similar to those in the strain Fujisawa. Further, a potential cytotoxicity of the isolate was confirmed, suggesting that marine mammal-isolated E. rhusiopathiae could possess strong pathogenic potential in other animals, including humans. These results would further increase our understanding on the risk factors for controlling zoonotic pathogens of emerging infectious diseases in captive or free-ranging cetaceans, and also provide important insight into the diversity of E. rhusiopathiae in animals.